Body composition of physically active women aged over 60 - Luz Beltrán Ramírez, Alba (2007)
With the objective of analyzing the body composition of physical active seniors: 116 women enrolled on the Program of Integrated Care for the older Adult in the Municipality of Chacao, Venezuela, were studied. Anthropometric variables were measured. Comparisons between variables revealed no statistical differences, with the exception of suprailiac skinfolds (p